The effective pattern design for children education to raise godly children based on Biblical standard - Pranata Santoso, Magdale (International Journal of Engineering and Technology, 2018)
In this digital era where individuals in the community turn out to be more secular and dependent on science and technology, some devoted Christian parents still want to teach their children to have godly characters. These parents assume that the Bible ought to be the basis of educating their children. They need an effective pattern design to teach their children in the light of the Bible since their early age. Various samples of parents were selected based on the children’s age, gender, number of siblings, parents’ occupations, and church ministries. The number of parents was about forty. They focused on teaching their children based on Biblical standard. The procedure began with the step of exploration, in which the indicators were determined. The characters of their children had been described before starting the observations. Parents employed the pattern design of character education that was adopted from the childhood of some Bible heroes and Christian leaders in the Church History. Those models are individuals who have a Christ-like character and credibility. On the second half of the preparation year, the second observation was conducted to find out the difference and the development of their childrenâ€™s characters. The result is a significant change in the characters of their children. Children who encountered this pattern of character education showed better character traits. They developed the ability to communicate with a healthy emotion, to be obedient to the parents, and also to build better relationships with parents and siblings. Educating children based on Biblical standard can be an effective pattern design of children education. It is a recommended model to equip parents who want their children to have godly characters in the middle of the digital era and secular society. Â